If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(1 + x) = -147 (1 * 7 + x * 7) = -147 (7 + 7x) = -147 Solving 7 + 7x = -147 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 7x = -147 + -7 Combine like terms: 7 + -7 = 0 0 + 7x = -147 + -7 7x = -147 + -7 Combine like terms: -147 + -7 = -154 7x = -154 Divide each side by '7'. x = -22 Simplifying x = -22
| 20m^2-9m=0 | | 7(1+x)=-146 | | 6(6-8x)=4(6-10x) | | j^2-28j=0 | | -3x+7+7x+7=15 | | -4(n+4)=-24 | | 2533000/x/1277.59=27.68 | | f(-2)=3(-2)-9 | | 5*5*5*5=70 | | 17n^2-29n=0 | | -9x-7-4x-6=15 | | 1/4(5x-9)=3 | | 3w+8x-11y+4w+7x+4y= | | 8x^3-18x^2+4x= | | y=8000+4x | | -2ln(x)+ln(y)=ln(6) | | K(n+1)=3n+2 | | 1/2-x/9=2x-9/9 | | x=4x^7+2x^4-10x^3-5 | | 5x-7=5(x-4) | | 5p+8.8=13.7+4p | | -4(-7x+7)=0 | | 7(-1x+2)=-49 | | r-19=-39 | | 2x+7+4x=-5 | | 6x-16=48 | | 6x+1+3x=46 | | (2x+4)(3x+5)=0 | | 3x+=30 | | 5x-3+2x=-80 | | 7=3x-x+3 | | -14=-3x+7x+10 |